PENGARUH LATIHAN DRILL TERHADAP KETERAMPILAN SHOOTING BOLA BASKET PUTRI PADA EKSTRAKURIKULER SMA NEGERI 1 ANDONG - Muhammad Faris Farhan; Agustanico Dwi Muryadi; Karlina Dwijayanti (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
Basketball is a game sport with the aim of putting the ball into the basketball hoop. To be able to play the ball well it is necessary to perform movements or techniques well. Good movements lead to work efficiency and with regular practice can make movements better and more effective. In the game of basketball, to get these effective and efficient movements it is necessary to be based on a good and correct mastery of basic techniques. Judging from the existing problems, it is necessary to find a training model that can improve the ability of athletes to shoot. Therefore, this study aims to determine whether there is an effect of drill training on women's basketball shooting skills in the basketball extracurricular of SMA Negeri 1 Andong in 2022. Quantitative research method with experimental approach with One Group Pretest-Posttest Design design. The population as the object of a study is 28 female students who participated in training at the 2022 Andong State High School 1 Basketball Extracurricular. The research sample was on the Andong State High School Basketball Extracurricular Women's Players 1 with a total of 20 students. Sampling using Total Sampling technique. The instruments used are a close-range shooting skill test of five different points and perform an exercise program. Data analysis techniques used with t tests using the spss 26 application. The results of the data analysis show that: There is an influence of drill training on women's basketball shooting skills in the 2022 Andong State High School 1 Women's Basketball Extracurricular With a calculated t value of -4.370 < t table 2.09, and a signification value of 0.000? 0.05, with a percentage increase of 54.71%.